Valorization of Vineyard By-Products Through Vermicomposting: A Comparative Pilot-Scale Study with Eisenia fetida and Eisenia andrei - Tiago Azevedo; Elisabete Nascimento-Gonçalves; Henda Lopes; Catarina Medeiros; Virgílio Falco; João R. Sousa; Ana M. Coimbra; Marta Roboredo; Paula A. Oliveira; Maria C. Morais (Agronomy)
Vermicomposting aims to convert organic residues into valuable end products within a circular economy-based framework. Vineyards generate significant amounts of by-products, namely vine prunings (VPs), typically landfilled or incinerated, and rotten grape clusters (RGCs), which stay on the vines until removed by pruning. This pilot-scale study aimed to explore the role of two earthworm species (Eisenia fetida and Eisenia andrei) in transforming VP and RGC substrates by evaluating their physicochemical properties, phytotoxicity, and polyphenolic content before and after vermicomposting and the microbial activity at the end of the process. The substrates were vermicomposted in 2 L containers with coconut fiber (1:1 ratio) and 7.5 g of each earthworm species (clitellated and non-clitellated) per container for 100 days, with the earthworm biomass monitored every other week. Phytotoxicity was assessed using garden cress (Lepidium sativum L.) and lettuce (Lactuca sativa L.) seeds, and biological stability was assessed by microbial activity and polyphenolic content evaluation using the Folin–Ciocalteu method. The results showed that differences in the vermicompost properties were primarily substrate-dependent. The RGC-based vermicomposts exhibited higher electrical conductivity and P, K, S, and B levels, while the VP-based composts had higher C/N ratios. E. fetida produced vermicomposts with significantly higher K, Ca, and Mg contents and consistently lower phytotoxicity in germination assays with garden cress and lettuce, compared with E. andrei. Vermicomposting led to a decrease in polyphenolic content for both species. This study highlights the importance of earthworm species selection for vermicomposting vineyard residues. Further research should explore how these species perform with other residues to understand their suitability for producing high quality vermicomposts.